Pengaruh Pemberian Kompos Ampas Kelapa (Cocos Nucifera L.) terhadap Pertumbuhan dan Produksi Tanaman Tomat (Solanum Lycopersium L.) di Polybag - Ratna Dewi; Dina Yuliasty Lamefa; Bangun Joko Laksono; Sri Harimurti; Reza Yunistianti (Jurnal Riset Rumpun Ilmu Tanaman, 2025)
This research discusses the effect of coconut dregs compost (Cocos nucifera L.) on the growth and yield of tomato plants (Solanum lycopersicum L.) cultivated using polybag media. This research is motivated by the importance of utilizing organic waste, especially coconut dregs, which has not been utilized optimally. Coconut dregs contain organic materials and nutrients that have the potential to increase soil fertility and improve the structure of the planting medium, so it is expected to support the vegetative and generative growth of tomato plants. The research design used was a Randomized Block Design (RBD) with six treatments and four replications. The treatments given were different doses of coconut dregs compost, namely P0 (control without compost), P1 (100 g/polybag), P2 (200 g/polybag), P3 (300 g/polybag), P4 (400 g/polybag), and P5 (500 g/polybag). The parameters observed included plant height, stem diameter, fresh weight, number of fruits per plant, root length, and estimated yield per hectare. The results showed that the application of coconut pulp compost significantly affected several growth parameters, such as plant height, stem diameter, and fresh weight. However, no significant effect was found on the number of fruits per plant or yield per hectare. The most prominent response was seen in the root length parameter, which showed a significant increase with increasing compost dosage. From the observations, the best treatment was at a dosage of 300 g/polybag (P3), which provided an optimal balance between vegetative growth and potential generative yield.